Influência cultural no valor subjetivo em negociação: estudo comparativo entre Bolívia e Brasil - Arteaga, Roger Manuel Bruno (2010)
This quantitative research is an exploratory study of subjectivity in negotiations with a view to ascertaining the extent to which national culture affects the subjective values of individuals in a negotiation. Data collection was developed in Bolivia and Brazil, using a questionnaire as an instrument of data collection, the SVI method to measure what the people value subjectively when they negotiate. The results were coded and through a statistical analysis it was evident that there are similarities and differences compared what Bolivians and Brazilians valued subjectively when they negotiate. The results were coded and by statistical analysis it became clear that there are similarities and differences in relation to the Bolivians and Brazilians valued subjectively. Concluding that both negotiators valued the satisfaction of the outcome of the negotiation, although satisfaction levels show a slight difference between them. There is a clear difference between Bolivia and Brazil regarding the perception of itself and, finally, negotiators valued a good relationship in negotiation. This is explained by the influence that national culture exerts on the negotiators in each country.